Offshore fears and onshore risk: Exchange rate pressures and bank volatility contagion in the People's Republic of China - Jennifer Lai; Paul D. McNelis (Asian Development Bank (ADB), 2019)
This paper shows that signals from the offshore Hong Kong, China spot market for the currency of the People's Republic of China (PRC), the renminbi (listed as CNH), directly affect the volatility of share prices of PRC banks and the overall risks to banking stability in the country. This is especially so amid heightened uncertainty about global trade of the PRC. Thus, CNH market volatility is a leading indicator of onshore PRC banking sector volatility. The results suggest that further offshore exchange market movements arising out of news such as increasing trade friction with the United States will generate greater volatility in the PRC's banking sector. Far from being a shock absorber for the financial system of the PRC, the CNH market appears to be a shock transmitter of risk from offshore economic policy uncertainty to the PRC's banking system.
Keywords: F31; G21; O24; 330; banking stability of the PRC; CNH market; currency of the PRC; exchange rate pressures; offshore exchange markets